Conservation implications of behavioural interactions between the Giant African Snail and a Native Brazilian species. Issue 3 (4th May 2017) - Miranda, Marcel; Pecora, Iracy
Abstract : The Giant African Snail Achatina fulica is widely considered one of the most invasive species in the world. Megalobulimus paranaguensis is a snail endemic to the Brazilian Atlantic Rainforest. Data on possible interactions between A. fulica and terrestrial mollusc species are scarce. We tested whether the presence of A. fulica affects the behaviour of M. paranaguensis . We put three individuals of A. fulica and three individuals of M. paranaguensis in the same aquarium and quantified the time spent in seven behaviours, during three nights ( n = 72 individuals for A. fulica and M. paranaguensis ). We also tested the effect of sexual maturity, putting juvenile and adult individuals of both species in the same aquarium. We found behavioural differences between species, among individuals exposed to interspecific interactions and in interactions between these factors, but there was no difference in behaviour between juveniles and adults in the same species and between species. Achatina fulica changed its behaviour in interspecific interaction, becoming more active than usual, but M. paranaguensis did not change its behaviour in the presence of the alien species. Our results show that interspecific interaction has an effect on the behavioural patterns of the alien species, and the main factor negatively impacting Megalobulimus populations in Brazil is probably the non-specific control of A. fulica and the alteration and destruction of its habitats.